Fatty acid metabolism-related signature suggests an oncogenic role of TEKT1 in endometrial cancer - Zhikai Xiahou; Hong Xiao; Yafeng Song; Xin Xu (Taiwanese Journal of Obstetrics & Gynecology)
Objective: The study aims to construct a prognostic signature to detect the molecular interaction between the fatty acid metabolism and the progression of endometrial cancer. Materials and methods: A total of 309 fatty acid metabolism relative genes were analyzed in the endometrial cancer cohort from The Cancer Genome Atlas. Dataset GSE216872 was applied for external validation. The R program was chosen to detect the expression of FAMRGs and execute GO/KEGG analysis. Considering the clinical information and pathological features, a prognostic gene signature was constructed using LASSO Cox regression analysis. According to FAM risk score, endometrial cancer patients were divided into high and low FAM-risk score groups. By differential expression analysis and cytoscape, TEKT1 was identified as the hub gene. Functional enrichments explored the biological process TEKT1 participated. Cellular proliferation, clone formation, migration, invasion, cycle, and apoptosis were assessed to detect the effect of TEKT1 in endometrial cancer. Co-immunoprecipitation and Western blot were performed to determine the mechanism of TEKT1. Results: A prognostic signature based on 10 FAMRGs (ACACB, PTGIS, BMPR1B, DHCR24, FAAH, GPX1, GPX4, INMT, PON3, PPT2) was generated using Lasso Cox hazards regression analysis in TCGA. TEKT1 was identified as the gene related to fatty acid metabolism. Next, we demonstrated that TEKT1 was highly expressed in endometrial cancer tissues in CPTAC and was mainly involved in the cell cycle and biosynthesis of unsaturated fatty acids. Ex-vivo experiments revealed that TEKT1 promoted proliferation, migration, and invasiveness while inhibiting apoptosis. Further experiments demonstrated that TEKT1 might promote fatty acid synthesis by binding to AMPK-γ for ACC and FASN downregulation. Conclusion: A reliable predictive signature based on genes related to fatty acid metabolism in endometrial cancer was conducted, wherein TEKT1 was mainly implicated as the primary gene of interest. TEKT1 showed affinity to AMPK-γ and probably promoted FA synthesis in endometrial cancer.